Illegal grain market in Ukraine: Harvesting war opportunities - Мельничук, Тетяна Володимирівна; Мельничук, Т. В.; Melnychuk, Tetiana V. (Oxford : Elsevier Ltd., 2025)
Based on empirical evidence, this research: highlights the timeline of changes in Ukrainian agricultural sector since the onset of the full-scale war in 2022 and the maritime blockade affecting exports; examines the relevant transformation of the illegal grain market amid these extraordinary turbulent circumstances; describes the key components of the heterogeneous illegal grain market, which includes the export of "black" grain through the grain corridor and trade in grain as a looted commodity from the occupied territories; identifies the role of organized crime and corruption in illegal transactions of wartime, considering the pre-existing models of the shadow economy functioning. The findings of this research may serve as a theoretical and methodological framework for studying scenarios of illicit economies in the context of armed conflicts and other systemic crises at both national and transnational levels.
Melnychuk T. Illegal grain market in Ukraine: Harvesting war opportunities / T. Melnychuk // Journal of Economic Criminology. – Oxford : Elsevier Ltd., 2025. – 8, № 100160. - 9 p. URL: https://doi.org/10.1016/j.jeconc.2025.100160
Keywords: Organized crime; Illicit economies; Black grain; Illegal trade; Shadow market; Corruption War; Ukraine